THE UNION DEFENCE FORCE ENTERTAINMENT GROUP IN THE MIDDLE EAST - Swift, M. (Scientia Militaria - South African Journal of Military Studies, 2012)
In November 1941, Major Myles Bourke flew from South Africa to Cairo to investigate the possibilities of sending South African concert parties to the Middle East. He was accompanied by Capt (then Lieut) Mrs Sybil Gaiger.